2020
DOI: 10.1101/2020.06.20.163006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptional response of signalling pathways to SARS-CoV-2 infection in normal human bronchial epithelial cells

Abstract: AcknowledgementsEnes Ak is funded by The Scientific and Technological Research Council of Turkey (TÜBİTAK) 116S388 and The Turkish Directorate of Health Institutes (TÜSEB) 2019-TA-01-3936. We thank O.Veli for the list of cytokines. Conflict of InterestWe declare no conflict of interest. 2 ABSTRACT SARS-CoV-2 virus, the pathogen that causes Covid-19 disease, emerged in Wuhan region in China in 2019, infected more than 4M people and is responsible for death of at least 300K patients globally as of May 2020. Iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…In bronchial epithelial cells infected with SARS-CoV-2, DEGs are enriched for members of pathways related to NF-κB, TNF-α, and IL-17 signaling. Specific genes shared by these pathways include MMP9 , ICAM1 , CSF3 , and IL6 ( Enes and Pir, 2020 ). A protein-protein interaction network of DEGs shared between COVID-19, MERS, SARS, H1N1, and Ebola identifies ICAM1 , VEGFA , MMP9 , IL6 , TNF , IL-8 , IL1B , STAT1 , TLR2 , TLR1 , IRF7 , and CXCL1 as hub genes ( Alsamman and Zayed, 2020 ).…”
Section: Adhesion and Tissue Retention Of Inflammatory Leukocytesmentioning
confidence: 99%
“…In bronchial epithelial cells infected with SARS-CoV-2, DEGs are enriched for members of pathways related to NF-κB, TNF-α, and IL-17 signaling. Specific genes shared by these pathways include MMP9 , ICAM1 , CSF3 , and IL6 ( Enes and Pir, 2020 ). A protein-protein interaction network of DEGs shared between COVID-19, MERS, SARS, H1N1, and Ebola identifies ICAM1 , VEGFA , MMP9 , IL6 , TNF , IL-8 , IL1B , STAT1 , TLR2 , TLR1 , IRF7 , and CXCL1 as hub genes ( Alsamman and Zayed, 2020 ).…”
Section: Adhesion and Tissue Retention Of Inflammatory Leukocytesmentioning
confidence: 99%
“…In bronchial epithelial cells infected with SARS-CoV-2, DEGs are enriched for members of pathways related to NF-kB, TNF-a, and IL-17 signaling. Specific genes shared by these pathways include MMP9, ICAM1, CSF3, and IL6 (Enes and Pir, 2020). A protein-protein interaction network of DEGs shared between COVID-19, MERS, SARS, H1N1, and Ebola identifies ICAM1, VEGFA, MMP9, IL6, TNF, IL-8, IL1B, STAT1, TLR2, TLR1, IRF7, and CXCL1 as hub genes (Alsamman and Zayed, 2020).…”
Section: Adhesion and Tissue Retention Of Inflammatory Leukocytesmentioning
confidence: 99%
“…In addition, in postmortem lung examinations of two severe and critically ill COVID-19 patients, the ACE2 protein levels were up-regulated, compared to the adjacent normal lung tissue [ 279 ]. In other recent studies, neither down- nor upregulation of ACE2 was observed in human cell lines infected with SARS-CoV-2 [ 228 , 229 , 280 ]. In COVID-19 patients, plasma levels and enzymatic activity of ACE2 were found increased [ 281 , 282 ] or not altered [ 278 , 283 , 284 ].…”
Section: The Roles Of Ace2 and Angiotensin II In Coronavirus-induced mentioning
confidence: 84%